Effects of Various Citrus Fiber Coatings on the Color, Texture, and Sensory Properties of Chicken Nuggets - Baris Yalinkilic; Ayhan Cigdem (International Journal of Gastronomy Research)
Wastes from the fruit juice industry are sources rich in functional compounds like dietary fiber. The present study aimed to investigate the suitability of dietary fibers derived from the orange, lemon, and grapefruit juice production wastes in the production of chicken nuggets as a coating material. In the control group, nugget samples were coated with breadcrumbs. Obtained chicken nuggets were analyzed for color, texture, pH, and sensory properties. The results indicated that the use of dietary fiber from different sources had a statistically significant effect on the pH and L*, a*, and b* values of the product before and after cooking at the level of p < 0.01. Particularly, the use of lemon and grapefruit fiber decreased the pH value of the samples significantly, whereas the usage of grapefruit fiber increased the a* value of both raw and cooked samples significantly. The results of the sensory analysis of the cooked samples revealed that except for salinity and juiciness, all sensory parameters were influenced significantly (p < 0.05) by the use of dietary fiber, and the grapefruit-coated samples had a more bitter taste compared to the other groups. In terms of overall acceptability scores, the lowest mean value was determined in the samples coated with grapefruit fiber. All texture parameters except adhesiveness and springiness were influenced by the use of different dietary fibers in cooked samples (p < 0.05).